Juan Moreira: Romantic Outlaw, Liberal Hero. Issue 1 (2nd January 2019) - Dabove, Juan Pablo
Abstract : Since its appearance in 1879–1880, Juan Moreira has been read as an illiberal novel, casting its eponymous hero (the historical bodyguard and electoral henchman of the same name) as a metaphor for the plight of variously-defined subalterns in liberal and neoliberal Argentina, and a condemnation of the social order they brought about. Contrary to that assumption, and reading the novel in its original context (the newspaper La Patria Argentina, in the months leading up to the Buenos Aires rebellion that would settle the fate of Buenos Aires, and end the cycle of civil wars in Argentina), the article argues that Moreira should be read as an strictly liberal novel, inventing a version of the gaucho not as a premodern barbarian (i.e. Sarmiento's version) but as the embodiment of a modern liberal notion of subject (and citizen, even citizen-in-arms), produced by a functional market economy and a modernizing state, whose descent into criminality is a consequence and a cautionary tale not of the evils of the liberal order, but of what for Gutiérrez was the illiberal (at the same time conservative and barbaric) embodied in his political opponents presidents Nicolás Avellaneda and Julio Argentino Roca.